Eye features and retinal photoreceptors of the nocturnal aardvark (Orycteropus afer, Tubulidentata) - Leo Peichl; Sonja Meimann; Irina Solovei; Irene L. Gügel; Christina Geiger; Nicole Schauerte; Karolina Goździewska-Harłajczuk; Joanna E. Klećkowska-Nawrot; Gudrun Wibbelt; Silke Haverkamp (PLoS ONE, 2025)
The nocturnal aardvark Orycteropus afer is the only extant species in the mammalian order Tubulidentata. Previous studies have claimed that it has an all-rod retina. In the retina of one aardvark, we found rod densities ranging from 124,000/mm² in peripheral retina to 214,000/mm² in central retina; the retina of another aardvark had 163,000 – 245,000 rods/mm². This is moderate in comparison to other nocturnal mammals. With opsin immunolabelling we found that the aardvark also has a small population of cone photoreceptors. Cone densities ranged from about 300 to 1,300/mm² in one animal, and from 1,100 to 1,600/mm² in a limited sample of the other animal, with a central-peripheral density gradient and some local variations. Overall, cones comprised 0.25-0.9% of the photoreceptors. Both typical mammalian cone opsins, longwave-sensitive (L) and shortwave-sensitive (S), were present. However, there was colocalization of the two opsins in many cones across the retina (35 – 96% dual pigment cones). Pure L cones and S cones formed smaller populations. This probably results in poor colour discrimination. Thyroid hormones, important regulators of cone opsin expression, showed normal blood serum levels. The relatively low rod density and hence a relatively thin retina may be related to the fact that the aardvark retina is avascular and its oxygen and nutrient supply have to come from the choriocapillaris by diffusion. In contrast to some previous studies, we found that the aardvark eye has a reflective tapetum lucidum with features of a choroidal tapetum fibrosum, in front of which the retinal pigment epithelium is unpigmented. The discussion considers these findings from a comparative perspective.